Pengolahan Limbah Yeast Mud Menjadi Pupuk Organik Padat Menggunakan Metode Composting Aerob - Amelia Putri Kusherawati; Clareta Rahmawati Maudy; Ketut Sumada; Caecilia Pujiastuti; Srie Muljani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Bioethanol is one of the alternative materials that can reduce dependence on non-renewable fuel oil. The process of making bioethanol produces by-products in the form of waste. Yeast mud is solid waste from the initial precipitation process of ethanol production. Yeast mud contains organic carbon of 39.33%, total nitrogen as nitrogen compounds of 1.76%, and a C/N ratio of 22. The organic carbon content contained in yeast mud exceeds the 2018 SNI value of a maximum of 32%. This study aims to determine the time needed to produce solid organic fertilizer in accordance with the Indonesian National Standard. The parameters used to determine the quality of solid organic fertilizer produced are C-Organic content, Nitrogen content, and C/N ratio. The method used in this research is aerobic composting with variations in the mass of yeast mud waste (1 kg; 2kg; 3 kg; 4 kg; and 5 kg) and variations in composting time (3; 4; 5; 6; 7 days), as well as an aeration rate of 1.5 l/min. The results showed that the C-Organic content that met the maximum SNI standard of 32% was obtained under the condition of a mass of yeast mud waste of 1 kg with a time of 5 days with a C-Organic content of 31.45% and a mass of yeast mud waste of 2 kg with a time of 7 days with a C-Organic content of 31.96%.